2020
DOI: 10.1139/apnm-2019-0129
|View full text |Cite
|
Sign up to set email alerts
|

Use of consumer monitors for estimating energy expenditure in youth

Abstract: The purpose of this study was to compare energy expenditure (EE) estimates from 5 consumer physical activity monitors (PAMs) to indirect calorimetry in a sample of youth. Eighty-nine youth (mean (SD); age, 12.3 (3.4) years; 50% female) performed 16 semi-structured activities. Activities were performed in duplicate across 2 visits. Participants wore a Cosmed K4b2 (criterion for EE), an Apple Watch 2 (left wrist), Mymo Tracker (right hip), and Misfit Shine 2 devices (right hip; right shoe). Participants were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 22 publications
2
10
2
Order By: Relevance
“…Another important finding is that the present study showed a contrary result to a previous finding that the Apple Watch significantly underestimated AEE in youth [ 21 ]. The study by LaMunion et al reported that the Apple Watch significantly underestimated AEE by 45% (mean difference: −121.8 kcal) and had more than 40% measurement error for AEE estimates compared to indirect calorimetry in youth [ 21 ].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Another important finding is that the present study showed a contrary result to a previous finding that the Apple Watch significantly underestimated AEE in youth [ 21 ]. The study by LaMunion et al reported that the Apple Watch significantly underestimated AEE by 45% (mean difference: −121.8 kcal) and had more than 40% measurement error for AEE estimates compared to indirect calorimetry in youth [ 21 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Another important finding is that the present study showed a contrary result to a previous finding that the Apple Watch significantly underestimated AEE in youth [ 21 ]. The study by LaMunion et al reported that the Apple Watch significantly underestimated AEE by 45% (mean difference: −121.8 kcal) and had more than 40% measurement error for AEE estimates compared to indirect calorimetry in youth [ 21 ]. However, the present study showed that the Apple Watch 3 similarly estimated AEE (mean difference: −3.8 kcal) with a relatively low measurement error (4%) compared to the indirect calorimetry in children.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…One study investigated physical activity measures relative to accelerometers in children 10-18 years old with congenital heart disease, [24] another investigated sleep relative to lab-based polysomnography (PSG) in healthy adolescents older than 12 years old, [15] and another investigated energy expenditure relative to indirect calorimetry in healthy adolescents older than 13 years old. [25] The results from these studies are mixed, yet with increasing concern about the importance of physical activity and sleep in youth, validated, cost-effective and appealing instruments are needed for studies of youth health.…”
Section: Plos Onementioning
confidence: 99%